Analisis Perhitungan Pajak Penghasilan PPh Pasal 21 dan PPh Pasal 23 Terhadap Pajak Terutang Badan : Studi Empirik : PT. Hang Sung Electronic Indonesia - Tony Renhard Sinambela; Natrion; Elianur (Mulia Pratama, 2022)
This study aims to determine the amount of Article 21 Income Tax and Article 23 Income Tax paid by PT. Han Sung Electronic Indonesia and to find out whether Income Tax Article 21 and Income Tax Article 23 affect the Corporate Tax Payable of PT. Hansung Electronic Indonesia. This research method uses a qualitative research approach, namely collecting data, processing data, then drawing conclusions. This research shows the comparative study between the calculation of Income Tax Article 21 using the Net method and the Gross Up method and the calculation of Income Tax Article 23. The type of data used is secondary data, the data is obtained indirectly or through other parties. This study uses descriptive analysis method by collecting data, processing and analyzing data in order to obtain an overview of the problem under study. The results of this study indicate that Income Tax Article 21 by using the Net and Gross Up method is the most efficient by using the Gross Up method or the provision of allowances in the amount of the tax payable resulting in efficiency of corporate income tax. And Income Tax Article 23 is obtained in the amount of Rp. 75.980,500 from Dividends, and Income Tax Article 23 on Accounting, Bookkeeping and Attestation Services of Financial Statements amounting to Rp. 418.000. based on Articles 17 and 31 E of Law Number 36 of 2018 concerning Income Tax the amount of Corporate Income Tax Payable at PT. Hansung Electronic Indonesia Rp.652.269.738.